2020
DOI: 10.3389/fneur.2020.567984
|View full text |Cite
|
Sign up to set email alerts
|

Resting Heart Rate Variability Is Associated With Subsequent Orthostatic Hypotension: Comparison Between Healthy Older People and Patients With Rapid Eye Movement Sleep Behavior Disorder

Abstract: Background: Orthostatic hypotension (OH) caused by autonomic dysfunction is a common symptom in older people and patients with idiopathic rapid eye movement sleep behavior disorder (iRBD). The orthostatic challenge test is a standard autonomic function test that measures a decrease of blood pressure during a postural change from supine to standing positions. Although previous studies have reported that changes in heart rate variability (HRV) are associated with autonomic dysfunction, no study has investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 81 publications
(110 reference statements)
0
5
1
Order By: Relevance
“…The explanation for this could be that HRV is closely related to cardiac autonomic function, while the CVS domain in the NMSS questionnaire mostly concerns orthostasis, which more accurately represents peripheral vascular autonomic function, or it could be that the subjective nature of questionnaire--assessed dysautonomia in NMSS does not reflect all of the aspects of CVS function. However, Sumi et al demonstrated that the decrease in HRV indices during the supine position can predict orthostatic hypotension, providing an alternative to the orthostatic challenge test [32]. While using the headup tilt test, Rocchi et al [33] described LF and LF/HF ratio as significantly higher in controls compared to iRBD, while we did not find statistically significant differences between both groups.…”
Section: Discussioncontrasting
confidence: 64%
“…The explanation for this could be that HRV is closely related to cardiac autonomic function, while the CVS domain in the NMSS questionnaire mostly concerns orthostasis, which more accurately represents peripheral vascular autonomic function, or it could be that the subjective nature of questionnaire--assessed dysautonomia in NMSS does not reflect all of the aspects of CVS function. However, Sumi et al demonstrated that the decrease in HRV indices during the supine position can predict orthostatic hypotension, providing an alternative to the orthostatic challenge test [32]. While using the headup tilt test, Rocchi et al [33] described LF and LF/HF ratio as significantly higher in controls compared to iRBD, while we did not find statistically significant differences between both groups.…”
Section: Discussioncontrasting
confidence: 64%
“…Although vascular dementia and neurodegeneration differs somewhat in their disease characteristics, they may share similar risk factors in their pathophysiology [ 2 , 63 ]. For example, reduced parasympathetic tone and sympathetic-vagal imbalance are related to orthostatic hypotension [ [64] , [65] , [66] , [67] ], which might be a culprit for transient cerebral hypo-perfusion and subsequent brain damage and subsequent development of both vascular dementia and Alzheimer's disease [ 61 , 63 ]. In addition, accumulated evidence has indicated that impaired autonomic activity is related to elevated blood pressure, including both pre-hypertension and hypertensive status [ [68] , [69] , [70] , [71] ], which has been shown to have a dose–response effect on risk of both vascular dementia and neurodegeneration at midlife [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy may derive from correlations among embedding dimensions and other features. In the fully featured hypotension model, which performs similarly to the more restrictive, best-performing model, blood pressure trends are supplemented by perfusion index and an HRV metric, which has previously been associated with incipient hemodynamic collapse 52 , 53 . Overall, our feature analysis suggests that the assessment period is highly valuable for the prediction of hypotension, as the best-performing model is able to correctly reclassify visits that would otherwise be erroneously flagged as high-risk by a simpler model solely relying on lower blood pressures at triage.…”
Section: Discussionmentioning
confidence: 99%